2016
DOI: 10.18280/ijht.340217
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Plate-Fin Heat Sink under Natural Convection Using a Particle Swarm Optimization Algorithm

Abstract: The purpose of this study is to find the optimal designing parameters of a plate-fin heat sink under natural convection using the Particle Swarm Optimization (PSO) Algorithm. Minimization of entropy generation rate under given space restrictions is considered as objective functions. All relevant design parameters for plate-fin heat sinks are the fin height, fin number, fin thickness. The constraints of the variables are set according to the suggestion structure design. And this three variables influence on ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Two types of heat-sink designs were experimentally tested a heat sink with one cut and a heat sink without cut for different heat inputs, from the experimental testing it was concluded that the heat sink with the cut had more temperature variations when compared to the heat sink without the cut. Liang et al [12] focused on finding the optimal design parameters such as fin height, fin number, fin thickness of a plate-fin heat sink under natural convection using the particle swarm optimization (PSO) Algorithm minimization written in MATLAB. The optimized heat sink results for the fin height, number of fins, fin thickness, base temperature were 44.8 mm, 25, 0.6 mm and 342.6241 K respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of heat-sink designs were experimentally tested a heat sink with one cut and a heat sink without cut for different heat inputs, from the experimental testing it was concluded that the heat sink with the cut had more temperature variations when compared to the heat sink without the cut. Liang et al [12] focused on finding the optimal design parameters such as fin height, fin number, fin thickness of a plate-fin heat sink under natural convection using the particle swarm optimization (PSO) Algorithm minimization written in MATLAB. The optimized heat sink results for the fin height, number of fins, fin thickness, base temperature were 44.8 mm, 25, 0.6 mm and 342.6241 K respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years saw the emergence of artificial intelligence methods like metaheuristic algorithm [15,16], local search algorithm [17], binary particle swarm optimization [18,19], and multi-objective tabu search algorithm [20,21]. In spite of some achievements, these methods are subject to certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the OPS raises a high demand for macro-optimization scheduling based on big data and features complex computation. Over the years, many intelligent optimization algorithms have been successfully applied to further improve the OPS's processing optimization ability, namely, competitive genetic algorithm (GA), directed ant colony algorithm (ACA), swarm intelligence (SI) information sharing algorithm, multiobjective simulated annealing algorithm [29][30][31][32][33][34]. Due to the high cost of field tests, computer simulation is the most common method for optimizing production line scheduling.…”
Section: Introductionmentioning
confidence: 99%